Pengobatan Tradisional Berbasis Ayat Al-Qur`an: Kajian Historis melalui Naskah Al-Mujarobat - Etika, Aini; Nayla Al Hafizd, Latifah Najwa; Habibi, Ahmad Zaki; Hudaidah, Hudaidah; Yati, Risa Marta (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
One of the strengths of Islam is the abundance of historical artifacts and research that we can find. In this regard, Islam provides guidance and teachings on healing using natural ingredients and prayers based on the Holy Qur`an. In this article, one form of traditional medicine is found in the Al-Mujarobat manuscript. This manuscript explains the meaning of a good life from the perspective of Islamic teachings, with the most interesting aspect being the discussion of traditional medicine along with its prayer guidelines. The research in this article uses a historical research method that includes heuristics, source criticism, interpretation, and historiography. The analysis in this article also involves philological studies as a specialized field in manuscript analysis. The findings of this research indicate that Islamic medical guidelines always follow the instructions of the Qur`an in seeking healing, performing therapy, and consuming medications.